WATERBIRD POPULATION ANALYSIS ON THE BANYUASIN PENINSULA SPTN REGION II REGION BERBAK AND SEMBILANG NATIONAL PARKS, BANYUASIN REGENCY - Mulyana, Deni; Aluyah, Cik; Heptiana, Erta (Universitas Muhammadiyah Palembang, 2021)
Waterbirds are migratory birds with the largest number in the world who always migrate to a place/region.. This study aims to determine the types and population of migratory and residents waterbirds(waders) on the Semenanjung Banyuasin SPTN region II Berbak and Sembilang National Parks, Kabupaten Banyuasin This study uses the Point Transect method, the number of bird populations is recorded directly and through estimates using the Block method. Based on observations, it was found that there were 3.743 water birds consisting of 3.240 migrant species and 503 resident species. From this number, after being identified, it is known that there are 20 species of migratory waterbirds and 11 species of resident waterbirds.